2018
DOI: 10.1038/s41388-017-0091-1
|View full text |Cite
|
Sign up to set email alerts
|

The miR-17/92 cluster is involved in the molecular etiology of the SCLL syndrome driven by the BCR-FGFR1 chimeric kinase

Abstract: MicroRNAs have pathogenic roles in the development of a variety of leukemias. Here we identify miRNAs that have important roles in the development of B-lymphomas resulting from the expression of the chimeric BCR-FGFR1 kinase. The miR-17/92 cluster was particularly implicated and forced expression resulted in increased cell proliferation, while inhibiting its function using microRNA sponges reduced cell growth and induced apoptosis. Cells treated with the potent BGJ389 FGFR1 inhibitor led to miR-17/92 downregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…Mechanistic studies then showed that circ-ITCH interacts with miR-214 and miR-17, but not miR-216b, miR-7 and miR-218; thus revealing that circRNA different functions rely on the specific context. Both miR-214 and miR-17 are wellknown oncogenes and are highly expressed in tumors [27,28]. Our data also showed these two miRNAs were uniformly up-regulated and negatively correlated with circ-ITCH in TNBC tissues; miR-214 and miR-17 interacted with the 3' UTR of their common target ITCH to reduce its expression [8,10].…”
Section: Discussionmentioning
confidence: 65%
“…Mechanistic studies then showed that circ-ITCH interacts with miR-214 and miR-17, but not miR-216b, miR-7 and miR-218; thus revealing that circRNA different functions rely on the specific context. Both miR-214 and miR-17 are wellknown oncogenes and are highly expressed in tumors [27,28]. Our data also showed these two miRNAs were uniformly up-regulated and negatively correlated with circ-ITCH in TNBC tissues; miR-214 and miR-17 interacted with the 3' UTR of their common target ITCH to reduce its expression [8,10].…”
Section: Discussionmentioning
confidence: 65%
“…The molecular etiology of SCLL is complex, with a diverse reorganization of gene expression patterns promoting stemness and suppressing differentiation, 4 , 16 supplemented by extensive changes in the micro RNA expression profile. 12 The constitutive, ligand-independent activation of FGFR1 kinases in SCLL suggests two possible roles in regulation of molecular function of genes and proteins depending on intracellular location. A cytoplasmic location, for example, potentially phosphoactivates other cytoplasmic proteins and a nuclear location can either activate nuclear proteins or bind DNA and function as a transcription factor or co-factor.…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle and apoptosis analysis was performed as previously described. 12 Quantitative reverse transcription polymerase chain reaction (qRT-PCR) and western blotting assays were carried out as described previously. 4 Detection of FGFR1 fusion kinase and its variants, used several different anti-FGFR1 antibodies designed against the human FGFR1 sequence; #9740 (Cell signaling, Inc) was raised against a recombinant protein specific to the FGFR1 carboxy terminus, ab76464 (Abcam) was raised against a synthetic peptide corresponding to aa 800 to the C-terminus and ab58516 (Abcam) was raised against a synthetic non-phosphopeptide derived from human FGFR1 around the phosphorylation site of tyrosine 654 (D-Y-Y P -K-K).…”
Section: Methodsmentioning
confidence: 99%
“…Since it has been established that PTEN is a specific target of miR-19a [7], PTEN and E2FS have been confirmed as miR-17-92 targets [16]. There are data showing a miRNA dynamically regulates CD8 T-cell differentiation from the naive stage to effector and memory phases, with short-lived effector cells expressing oncogenic miR-17-92 to high level, compared with the slower proliferating memory-fated cells [62]. A number of studies concluded that miR-17-92 regulates proliferation and survival via reduction in the expression of PTEN, a negatively regulating molecule, thereby lifting the suppression of the PI3K/AKT/mTOR signaling pathway.…”
Section: Target Gene Of the Mir-17-92 Clustermentioning
confidence: 99%
“…Faster acquisition of memory properties emerges as miR-17-92 levels are reduced. It is beneficial, therefore, to control miR-17-92 expression during immunization in order to optimize T-cell memory quantity and quality [62]. Increased proliferation upon miR-17-92 overexpression correlated with decreased expression of the tumor suppressor PTEN and increased PI3K AKT/mTOR signaling [62].…”
Section: Target Gene Of the Mir-17-92 Clustermentioning
confidence: 99%